Impact of Pharmacist-Led Diabetes Self-Care Education on Patients With Type 2 Diabetes in Pakistan: A Randomized Controlled Trial - Bukhsh, Allah; Khan, Tahir Mehmood; Phisalprapa, Pochamana; Duangjai, Acharaporn; Saokaew, Surasak; Nawaz, Muhammad Sarfraz; Ahmed, Hafiz Sajjad; Goh, Bey-Hing (Frontiers in Pharmacology, 2022)
Introduction There is a little evidence on efficacy of pharmacy-based interventions on clinical outcomes of type 2 diabetes mellitus (T2DM) patients in Pakistan. Objective To appraise the impact of pharmacist-led self-care education on glycemic control, self-care practices and disease knowledge of T2DM patients with poor glycemic control (HbA1c ≥ 7%). Methods In this 6-months, randomized controlled trial (RCT), n=75, T2DM patients seeking care at a diabetes clinic were randomized in to two groups. Intervention group (n=38) received two face-to-face educational sessions (at enrollment and on week 12), whereas control group (n=37) received usual care. Outcome measures such as glycemic control, self-care practices and disease knowledge were assessed at the time of enrollment and after 6-months in both groups. Results Thirty-three intervention and thirty-three participants from the control group completed the study. Mean glycated hemoglobin (% HbA1c) significantly reduced in the intervention group from 9.00±1.43 to 8.09±1.16 (p<0.01). However, no significant change was observed in the control group (9.20±1.24 to 8.93±0.97; p = 0.06). Cohen’s d effect size of the intervention on HbA1c was 0.78. Percentage of participants achieving glycemic control (HbA1c<7%) were significantly higher (p<0.05) in the intervention group as compared to the control group (twenty-four vs six), after 6 months of the trial. A significant (p<0.01) improvement in mean scores for disease knowledge and self-care activities was also observed in the intervention group participants, whereas no significant improvements (p>0.05) were observed in the control group. Conclusion The study demonstrated an improvement in glycemic control, disease knowledge and self-care activities of T2DM patients who received pharmacist-led educational intervention. The study findings support clinical significance of integrating pharmacy-based interventions in diabetes management.